261 A case of metastatic myxoid liposarcoma causing cardiac tamponade. (8th December 2021) - Cimino, Giuliana; Bisegna, Stefano; Cersosimo, Angelica; Amore, Ludovica; Vizzardi, Enrico; Lombardi, Carlo Mario; Raddino, Riccardo; Danesi, Rossella; Chiari, Ermanna; Repossini, Alberto; Metra, Marco
Abstract: Aims: Primary cardiac tumors are generally benign. In one series of over 12 000 autopsies, only seven cases of malignant primary cardiac tumors were identified, for an incidence of less than 0.1%. By comparison, metastatic involvement of the heart is over 20 times more common and has been reported in autopsy series in up to one in five patients dying of cancer. Myxoid liposarcoma (MLS) is the second most common subtype of liposarcoma and it usually occurs in deep tissues of the extremity, especially in the calf or thigh. Some tumors have round cell areas that represent histologic progression to high-grade tumours. Round cells, defined as > 5% of the total cells, are associated with higher malignancy and metastatic potential, resulting in an unfavourable outcome in patients affected. Patients with MLS tend to have metastases to extra pulmonary sites, such as abdominal wall, abdominal cavity, retroperitoneum, and bone, even in the absence of pulmonary metastases. Although several authors have reported a high proportion of extra pulmonary metastases of MLS, cardiac metastasis is extremely rare. Methods and results: We present a case of a young woman who underwent resection of calf liposarcoma with the onset of cardiac metastases after 18 years, with cardiac tamponade as a clinical onset. MRI confirmed the cardiac solid mass already evident on CT scan, located along the free anterior wall of the right ventricle in the mid-basal area; the lesion seemed to have pericardial implantation with the free wall of the right ventricle was not well cleaved by the lesion in the Cine-MRI sequences. However it was always visible in the post-contrast sequences without evident protrusion of the lesion into the cavity or signs of thrombosis. The parietal pericardium was located on the periphery of the lesion and was not recognizable in some points. The lesion consisted of two portions, a lower one in which some components with characteristics of adipose signal were recognizable, while the upper one was more solid and vascularized. There was persistence of inhomogeneous and diffuse late enhancement at the lesion level. PET revealed pathological hyper accumulations of radiopharmaceuticals in the heart lesion along the anterior wall of the right ventricle, with central hypocaptation area, possible expression of necrotic-colliquative phenomena. Other hyper accumulations were found in the mediastinal lymph node in the pre-carenal area. These findings were referable to the presence of glucose hyper metabolic tissue of suspected neoplastic significance. The patient temporarily declined surgical excision, but after one month, due to the worsening of her symptoms, she returned to emergency room: The CT scan showed a volumetric increase in cardiac mass with a vertical diameter of 8 cm and adhering to the right ventricle for 7 cm. Thanks to the possibility of surgery, patient underwent exeresis of the capsulated epicardial mass adhering to the anterior wall of the right ventricle and to the pericardium, with removal of the ventricular wall and reconstruction with a bovine pericardium patch and without postoperative complications. Conclusions: In MLS the time intervals between the onset of primary disease and cardiac metastasis were reported to be relatively long, ranging from 1 to 25 years. The initial site of metastatic disease in our patient was the heart: she had a solitary cardiac tumour that presented 18 years after the primary surgery in the absence of metastases at other sites. When a cardiac metastasis is found incidentally, it is usually incurable.